Pendampingan Pengenalan Online Marketing Upaya Keberlanjutan Usaha UMKM Desa Leuwimunding - Agus Yudianto; Tuti Yuliawati (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
In the MSME industry, one form of effort to help small businesses is in the form of encouragement so that MSME actors can immediately become adaptive to the changes that are occurring. Various forms of workshops have been carried out by the service team in Leuwimunding Majalengka village so that digital transformation for mentoring MSMEs can be realized immediately. However, as the number of MSMEs grows, it is increasingly crucial that support and cooperation from external parties, one of which is educational institutions, act as facilitators for the implementation of MSMEs so that more and more MSMEs are prepared to face the digital/online era, carrying out on-boarding and sales. active, increasing the scale of the business, and it is hoped that it will continue, at least to be sustainable and sustainable. The implementation of community service is expected to provide skills through digital marketing training so that MSMEs are able to design appropriate digital marketing strategies. The method of implementing the activity is that the first stage is carrying out Digital Marketing training. Then there is mentoring where MSMEs can implement the knowledge they have gained in training so that MSMEs have the skills to design and determine the right digital marketing strategy. Next is monitoring and evaluation to find out the progress of the digital marketing program that has been carried out.